TEACHING MATHEMATICS AND SCIENCES IN ENGLISH IN PILOT INTERNATIONAL STANDARD HIGH SCHOOLS IN INDONESIA - Setyorini, Andras; Sofwan, Ahmad (Language Circle: Journal of Language and Literature, 2011)
One of the ways to improve the quality of education in Indonesia is by initiating the program called Rintisan Sekolah Bertaraf Internasional (Pilot International Standard School-ISS). This program provides grants to selected schools to implement the teaching and learning process to comply with the international standards as in the developed countries. Some subjects, including Mathematics and Sciences are taught by using English as a medium of instruction in the classroom. Textbooks for these subjects have been prepared in both Indonesian and English. However, the teachers are not yet ready to conduct the teaching and learning activities in English, so there seems to be some problems in the classroom due to the lack of English proficiency among the teachers. With respect to this issue, the school can adopt Content-Based Instruction in which the students would learn the language as a by-product of learning about real-world and encourage the collaboration between subject matter teachers and English language teachers. ÃÂ  Key words: International Standard School, Mathematics, Sciences